Enhancing Students’ Performance Of Five Times Daily Prayers Amongst Polytechnic Students - Maizan binti Mohamad (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2017)
his study was conducted to enhance students’ performance towards performing their five times daily prayers amongst polytechnic students. 47 Semester One students from Diploma in Tourism and Management as well as Diploma Accountancy, June 2016 session of Politeknik Hulu Terengganu were involved in this study. The objectives of this research are to find out students’ awareness of the five times daily prayers; to identify students’ understanding about solah and third; and to increase students’ realization towards solah. The given pre-test showed that 50% of the students did not achieve the desired grade which was A. There were a few problems identified causing the students struggled in the test. The collection of data was done through the administration of a questionnaire, as well as pre-test and post-test. Actions taken were through the implementation of the PHT Fardhu Ain Module and Kem Pemantapan Fardhu Ain. The administered treatment has resulted in a significant increase of students’ performance of five times daily prayers among the students. 78.5% of the students scored A+ in the given post-test.